A Comparative Analysis of Life style of the Local People before and after the Construction of the Dams in the Sub Zone of Mendefera: A Case Study of Adi-Mengoti and Mai-Aron Dams - Afsar Alam, Mohammad; Khan, Masihulla (Journal for Geography, 2014)
Eritrea is one of the Sahelian countries in the Horn of Africa facing acute shortage of water. In areas where rainfall is low and unreliable, the construction of dams is utmost important for irrigation, domestic and livestock uses. Agriculture is the mainstay of Eritrean people; it has been playing a vital role in the process of economic development. It is estimated that about 75 per cent of the population depends on agriculture and allied activities. In such a country where agriculture is the backbone of the economy regular supply of water for irrigation is as important as the veins and arteries in the human body. In fact, dams serve multi purposes i.e. water supply for agriculture and domestic uses, flood control, hydro-power generation, navigation, fisheries and recreation activities. But in Eritrea, dams are mainly constructed to supply water for irrigation, domestic, industrial and livestock uses. This research paper is carried out to examine a comparative analysis of life style of the local people before and after the construction of the dams in the sub zone of Mendefera (Zoba Debub, Eritrea).